Exploring the Potential of Carbon Dots to Combat COVID-19 - Kotta, Sabna; Aldawsari, Hibah Mubarak; Badr-Eldin, Shaimaa M.; Alhakamy, Nabil A.; Md, Shadab; Nair, Anroop B.; Deb, Pran Kishore (Frontiers in Molecular Biosciences, 2020)
Viral diseases are considered as a global burden. The abolition of viral diseases is always a challenging task in medical research due to the high infectivity and mutation capability of the virus. The ongoing COVID-19 pandemic is still not under control even after several months of the first reported case and global spread. Neither a specific drug nor a vaccine is available for public use yet. In this regard, carbon dots could be considered as a recommended nanostructure by MOTHER NATURE. Tailoring them for specific purpose, by environment-friendly techniques, is a promising approach. In this review, we explore the possibility of carbon nano-dots to combat COVID-19 based on some reported studies. Carbon dots are photoluminescent carbon nanoparticles, smaller than 10 nm in dimension with a very attractive photostable and biocompatible properties which can be surfaced modified or functionalized. These photoluminescent tiny particles have captured much attention owing to their functionalization property and biocompatibility. In response to this pandemic outbreak, this review attempts to summarize the potential use of carbon dots in antiviral therapy with particular emphasis on their probable role in the battlefront against COVID-19 including their possible biosensing applications.